History of the plyometric training: A review in sport - Nelson Kautzner Marques Junior (Tanjungpura Journal of Coaching Research)
Background and Study Aim. From 1919 to 1930, the athletics coaches prescribed the first sessions of plyometric training for their athletes in Nothern and Eastern Europe. The objective of the review was to present the history of the development of plyometric training.